Follicular pityriasis versicolor-Rare variant of a common dermatological disease - Tasleem Arif; Shagufta Rather (Our Dermatology Online, 2015)
Pityriasis versicolor is a superficial fungal infection of the skin caused by yeast of the genus Malassezia. It is characterized by hypopigmented or hyperpigmented macules and patches usually involving the trunk [1]. The variants of pityriasis versicolor include hypochromic, hyperchromic, combination of hypo-hyperchromic, erythematous, circinate, atrophic and acral [2-4].